CO2 IN HAPLO-PHONOLITE MELT: SOLUBILITY, SPECIATION AND CARBONATE COMPLEXATION - Morizet Y.; Brooker R.A.; Kohn S.C. (My University, 2002)
CO2 solubility was measured in a synthetic iron-free phonolite (haplo-phonolite) by equilibrating melt with excess CO2 fluid in a piston cylinder apparatus for a range of pressures (1.0- 2.5 GPa) and temperatures (1300 to 1550°C). The quenched glasses were then analysed using a bulk carbon analytical method (LECO). The measured solubilities are between 0.65 and 2.77 wt.% for the range of conditions studied and show a negative correlation with temperature as reported for most other silicate melt compositions.A range of carbonate species are present within the glass, as well as minor amounts of molecular CO2. FTIR and NMR analyses suggest that carbonate is present as both 'network' and 'depolymerised' units as shown for relatively highly polymerised compositions in the model of Brooker et al. (2001b). The bulk CO2 analyses were used to calibrate the IR extinction coefficient for the carbonate groups. However, the results show that the values obtained for the glasses vary with the melt equilibration conditions, presumably because the ratio of the different carbonate species changes as a complex function of run pressure, temperature and quench rate. Thus the use of IR may not be a reliable method for the quantification of dissolved CO2 concentrations in natural glasses of 'intermediate' composition.